Analysis of digitalization of the economy of the Republic of Uzbekistan - Rakhmatullaeva Dilbar Olimovna (Zien Journals, 2022)
The rise of the digital economy is one of the characteristics of the 21st century. Digital technologies affect society and the economy in many ways, including through new means of communication and collaboration; new products with a strong service component; the role of information as a factor of economic growth; the automation of tasks using artificial intelligence (AI); and the emergence of new business models such as platforms. Therefore, digitization will fundamentally change the way we live and work together. This has consequences for the well-being and cohesion of society as a whole, as well as productivity, employment, skills, income distribution, trade, and environmental impacts for businesses in all sectors.
Keywords: E-commerce; digitalization; ICT; digital economy